Moderate Hyperkalemia Presenting As Sinus Arrest With Junctional Escape Rhythm From A Hospital With Resources Limited Setting: A Case Report And Narrative Review - Delta Iswara; Anggita Dian Karera; Satrya Yudha Dwi Putranto; Rois Hasyim (International Journal of Health Engineering and Technology, 2026)
Hyperkalemia is a potentially life-threatening electrolyte disturbance that can cause severe cardiac conduction abnormalities, even at moderate serum potassium levels, particularly in elderly patients with underlying cardiovascular disease. Management of acute hyperkalemia remains challenging, especially in resource-limited healthcare settings where advanced therapies such as urgent dialysis may not be readily available. We report a 77-year-old woman who presented with generalized weakness and recurrent syncope. Electrocardiography revealed sinus arrest with a junctional escape rhythm, and laboratory evaluation showed moderate hyperkalemia (6.84 mmol/L) accompanied by acute kidney injury, anemia, and mild metabolic acidosis. The patient had a history of anterior ST-elevation myocardial infarction and was receiving potassium-retaining medications. She was admitted to the intensive care unit and treated with protocol-based glucose–insulin therapy, intravenous calcium gluconate, adjunctive β-adrenergic agonists, and supportive care, without immediate access to dialysis. Serial ECGs demonstrated recovery of sinus rhythm, and serum potassium levels gradually normalized. This case illustrates that moderate hyperkalemia can precipitate severe bradyarrhythmias such as sinus arrest. Early recognition of ECG changes and prompt, protocol-driven management can result in favorable outcomes, even in resource-limited settings without immediate dialysis availability.